ENT 530 Social Media Portfolio: Dim Sum by Aishah Shahudi / Siti Nur Aishah Shahudi - Shahudi, Siti Nur Aishah (2021)
Dim Sum by Aishah Shahudi was establish by Siti Nur Aishah binti Shahudi to satisfied the customers appetite and we are open as request of our customers. Our main objective is to provide various types of dim sum so that our customers can taste any types of dim sum that they want to try. We have try our best to give the most delicious and satisfying dim sum to the customers. This product also is also liked by many customers because of the delicious taste. This product also get a lot of attention from customers due to the price that are affordable and reasonable price. Other than that, this product also provide a good insight for the continuation of sale to the customers. Since early of its opening, Dim Sum by Aishah Shahudi has sold so many of packages with nine different types of dim sum to the customers. The customers also keep repeat their orders because the dim sum taste so good.